Catalysing actionable knowledge for youth entrepreneurship: Experience of VETSARK (Nigeria) - Blessing, Mene (Technical Centre for Agricultural and Rural Cooperation, 2018)
Mene Blessing, Co-Founder and CEO of Vetsark (Nigeria) shares his entrepreneurial journey and give some advice to youth.